The role of excess surface water in shaping landscape character - Varga, Dalma Erzsébet; Módosné Bugyi, Ildikó; Bíró, Tibor; Hubayné Horváth, Nóra (4D Journal of Landscape Architecture and Garden Art, 2025)
An increasingly important mission nowadays is to conserve water resources and implement water retention measures, as also set out in the nature restoration regulation adopted by the European Union. Approximately one third of Hungary’s territory was periodically or regularly waterlogged before river regulation. As a result of the flood management works of the 18th and 19th centuries, the process of drying out and the phenomenon of excess surface water flooding began. Today, this affects about 60% of the country’s cultivated flatland, to a greater or lesser extent. Excess surface water may occur periodically within a given area and plays a major ecological role, with a significant impact on the landscape. The main objective of our research is to identify and analyse the role of areas exposed to excess surface water inundation in shaping landscape character with a value-based approach. Using geospatial methods, we compared the database of landscape character areas in Hungarian national landscape character research with the excess surface water areas dataset, and separately analysed the correlations between the two categories according to the frequency of excess surface water inundation. To confirm these results, we also analysed the overlap between the areas exposed to excess surface water inundation and landscape scenery protection areas. Our results show that the role of areas exposed to excess surface water inundation in influencing landscape character and shaping the landscape is decisive and can be supported by figures. Excess surface water increases landscape diversity, especially in homogeneous agricultural landscapes, and also helps enhance biodiversity. Our analyses grouped landscape character types according to their degree of hydrological influence, thus we distinguished how water-dominant or water-influenced landscape character areas or landscape character areas not influenced by water relate to areas exposed to excess surface water inundation. The results show that more than a fifth (21.36%) of the areas exposed to excess surface water were classified as either water-dominant or water-influenced landscape character areas. Consequently, excess surface water played a role in the classification of landscape character types, without being an indicator for landscape character area designation. In terms of the typical landscape character classification of areas exposed to excess surface water inundation, it can be concluded that it is mainly found in higher proportions in homogeneous agriculture-dominant landscapes defined by arable land and grassland. As excess surface water is mainly a water resource that periodically forms at local level, its landscape-level impacts are less pronounced, but its role in shaping the landscape and landscape character of these areas on a regional scale cannot be ignored.